Pengembangan Keterampilan Abad Ke-21 Dalam Pembelajaran Geografi - Nur Hasnah (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
The 21st century learning paradigm is characterized by the development of four skills, namely creative and innovative thinking, critical thinking and problem solving, communication, and collaboration. The aim of learning Geography globally is to equip students with knowledge, skills, and a geographical perspective. Geography learning must refer to the 21st century learning paradigm which is characterized by the characteristics of geography as a synthetic-integrative science. There are three approaches or perspectives in geography, namely spatial, environmental, and regional complex. In its implementation in 21st century learning, Geography lessons use a scientific approach. The scientific approach seeks to encourage students to think critically and creatively through 5M activities which consist of observing, asking questions, making hypotheses, exploring, and making conclusions. Through a scientific approach, students can be actively involved in the discovery process and build a deep understanding of the concepts being studied.